Intercultural Management and the Process of International Acquisitions: A Study of Turkish Firms - Karasahin, Mehmet Burak (My University, 2013)
This research mainly focuses on the “Intercultural management issues took place during the process of international acquisitions”. The purpose of this research mainly is to focus on the intercultural conflicts but this study also focuses on recommendations on the basis of research findings. As this study is unique in its nature as it is not case based, therefore it is not related to only one company. This study discusses the intercultural management issues and cultural differences in the Turkish acquisitions. Research focuses on finding the main dimensions and elements of intercultural management issues which cause troubles in the successful acquisition process. By considering the phenomenology philosophy, this study used the inductive reasoning approach for interpreting the phenomena. This study conducted the self-administered semi structured interviews from the HR personal of acquirer firms by following the qualitative strategy for investigating the phenomena. The interview results highlight the fact that cultural differences and intercultural management issues significantly impact the acquisition process. This study helps the professionals to know more about the current intercultural management conflicts arising in international acquisition.
Keywords: fi=Master's Degree Programme in International Business|